Correlation of Virtual Classroom Intervention with Help Seeking Behavior in Adolescents with Anxiety and Depression in Ketapang Regency - Utin Susmayani; Zahroh Shaluhiyah; Antono Surjoputro (Postgraduate, University of Mataram, 2025)
There were 9,162,886 cases of depression with a prevalence of 3.7 percent among Indonesian adolescents. However, there is no specific intervention to prevent and overcome this problem, especially in the field of mental health promotion. This study aims to determine the effect of health education through virtual classes on anxiety and depression on the knowledge and attitudes of adolescents in Ketapang Regency. The method used was quasi experimental pre and post with control and intervention groups. The population in this study were high school/equivalent adolescents in Ketapang Regency with a total sample of 80 divided into 40 control groups and 40 intervention groups. The variable used is help-seeking behavior. The intervention used is a Virtual Class involving 2 professional experts in the field of adolescent mental health. The intervention was carried out 2 times in a duration of 14 days. Before the intervention, a pretest test was conducted. The media used are cellphones, laptops or gadgets that can operate Zoom Meeting. Analysis of results using univariate, bivariate and multivariate tests with the help of the SPSS version 25.0 application. The results of the analysis showed that there were differences in behavior in respondents before and after the intervention in the intervention group. The behavior variable of the intervention group before and after the intervention has a significance value of 0.000 with the Wilcoxon test, which means that there is a difference in value after the intervention. There was an improvement in behavior. Overall, the behavior of the intervention group has increased compared to the control group which tends to stagnate. After the Spearmann correlation analysis test was carried out, the results of the behavior variable were found to be 0.008 with a correlation coefficient of 0.416. These results indicate that in the behavior variable there is a fairly good relationship. Virtual classes for high school teenagers in Ketapang improve behavior and have a fairly close relationship.